2022
DOI: 10.1155/2022/5435656
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Risk-Prediction Scoring System for Sepsis among Patients with Acute Pancreatitis: A Retrospective Analysis of a Large Clinical Database

Abstract: Background. The prognosis is poor when acute pancreatitis (AP) progresses to sepsis; therefore, it is necessary to accurately predict the probability of sepsis and develop a personalized treatment plan to reduce the disease burden of AP patients. Methods. A total of 1295 patients with AP and 43 variables were extracted from the Medical Information Mart for Intensive Care (MIMIC) IV database. The included patients were randomly assigned to the training set and to the validation set at a ratio of 7 : 3. The chi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…In addition, it was previously proved that sepsis (positive blood culture) was a cause of death, as it could result in shock (usually needs vasoactive drugs) and organ dysfunction. [14–17] In addition, the results of the present study suggested that A baumannii infection was also a risk factor for death in patients with infected pancreatic necrosis after surgical intervention. A baumannii has become the main source of nosocomial infection, especially in intensive care unit.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, it was previously proved that sepsis (positive blood culture) was a cause of death, as it could result in shock (usually needs vasoactive drugs) and organ dysfunction. [14–17] In addition, the results of the present study suggested that A baumannii infection was also a risk factor for death in patients with infected pancreatic necrosis after surgical intervention. A baumannii has become the main source of nosocomial infection, especially in intensive care unit.…”
Section: Discussionmentioning
confidence: 60%
“…For example, the SOFA score mainly focuses on the function of multiple organ systems and does not specifically address the pathological and physiological characteristics of pancreatitis itself, thus may lack sensitivity or specificity ( 4 , 10 ). Similarly, although the GCS score and SIRS score reflect the patient’s level of consciousness and systemic inflammatory response, they may not fully consider the specific conditions of pancreatic tissue damage and inflammation in the prognosis assessment of pancreatitis ( 44 , 45 ). CAR takes Cr and Alb levels into account and reflects a combination of renal function and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis encompassing a total of 1295 AP patients, Feng et al [ 149 ] developed an independent predictive tool, known as a nomogram, to predict the likelihood of sepsis occurrence in this patient population. In this study, the predictive performance and clinical utility of the newly established nomogram surpassed those of other scoring systems such as SIRS, BISAP, SOFA, and qSOFA[ 149 ]. The innovative risk-prediction system could precisely estimate the likelihood of sepsis in AP patients, assisting clinicians in formulating personalized treatment strategies for the patients.…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
“…The innovative risk-prediction system could precisely estimate the likelihood of sepsis in AP patients, assisting clinicians in formulating personalized treatment strategies for the patients. By doing so, it not only alleviated the disease burden of the patients but also facilitated the reasonable distribution of medical resources, which was a crucial aspect of tertiary prevention[ 149 ]. The nomogram incorporated all the independent prognostic factors, including body temperature, phosphate, Ca 2+ , sodium, lactate, albumin, platelet count, urinary output, mean blood pressure, Glasgow Coma Scale, and Charlson Comorbidity Index[ 149 ].…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
See 1 more Smart Citation